2011
DOI: 10.1128/mcb.05574-11
|View full text |Cite
|
Sign up to set email alerts
|

TopBP1 Mediates Mutant p53 Gain of Function through NF-Y and p63/p73

Abstract: Nearly half of human cancers harbor p53 mutations, which can promote cancerous growth, metastasis, and resistance to therapy. The gain of function of mutant p53 is partly mediated by its ability to form a complex with NF-Y or p63/p73. Here, we demonstrate that TopBP1 mediates these activities in cancer, and we provide both in vitro and in vivo evidence to support its role. We show that TopBP1 interacts with p53 hot spot mutants and NF-YA and promotes mutant p53 and p300 recruitment to NF-Y target gene promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 48 publications
10
118
0
Order By: Relevance
“…The p53R273H protein mediates invasion towards EGF through its ability to inactivate p63, while, as shown here, invasion to HB-EGF can be mediated through a new and highly specific biochemical interaction with NRD1. Our observations that mutant p53 can cooperate with NRD1 to promote invasion are consistent with several recent studies [10][11][12]14,[16][17][18]32] that demonstrated a neomorphic ability of mutant p53 to promote invasion. One mechanism underlying this gain of function of mutant p53 is an inhibition of the p53 family member p63, thereby promoting invasion responses to two important growth factors; EGF [11] and tumour growth factor-b [10].…”
Section: P53/nrd1-driven Invasion Is P63/rcp Independentsupporting
confidence: 80%
See 1 more Smart Citation
“…The p53R273H protein mediates invasion towards EGF through its ability to inactivate p63, while, as shown here, invasion to HB-EGF can be mediated through a new and highly specific biochemical interaction with NRD1. Our observations that mutant p53 can cooperate with NRD1 to promote invasion are consistent with several recent studies [10][11][12]14,[16][17][18]32] that demonstrated a neomorphic ability of mutant p53 to promote invasion. One mechanism underlying this gain of function of mutant p53 is an inhibition of the p53 family member p63, thereby promoting invasion responses to two important growth factors; EGF [11] and tumour growth factor-b [10].…”
Section: P53/nrd1-driven Invasion Is P63/rcp Independentsupporting
confidence: 80%
“…Mechanisms underlying the oncogenic nature of mutant p53 include interaction or regulation of other transcription factors including p63, p73, NF-Y and VDR [12][13][14][15] or additional binding proteins such as TOPBP1, ANKRD11 and PIN1 [16][17][18]. Nearly all of the large number of interacting proteins reported in IARC p53 database [2] bind to wt-p53 and are therefore not good candidates for the neomorphic mutant hypothesis.…”
Section: Introductionmentioning
confidence: 99%
“…Other mechanisms of mutant p53 GOF include mutant-p53 complexes with Smad that fuel TGF-β-induced metastasis (7) and integrin recycling (8). Additionally, mutant p53 interacts with the vitamin D receptor and converts vitamin D into an antiapoptotic agent (9)(10)(11)(12)(13)(14). More recently, mutant p53 was reported to form transcriptional complexes on promoters of genes encoding several enzymes of the Mevalonate pathway, which increases metastasis of breast cancer cells (9).…”
mentioning
confidence: 99%
“…To confirm the functional link between ZDHHC5 and p53, we examined whether mutant p53 modulated ZDHHC5 expression, as most cancer-associated p53 mutations are associated with a loss of its transcriptional activity. Mutant p53 was capable of physical interaction with the transcription factor NF-Y; the gain-offunction induced by this protein complex was independent of the type of p53 mutation (27,28). Moreover, this interaction resulted in aberrant upregulation of ZDHHC5, whose promoter contains four potential NF-Y-binding sites.…”
Section: Discussionmentioning
confidence: 93%
“…2B). The most common frameshift and missense mutations in the p53 gene result in a gain of function and interaction of p53 with nuclear transcription factor (NF)-Y, which leads to aberrant transcriptional regulation of oncogenic factors (27,28). The 1-kb upstream region of the ZDHHC5 promoter contained four potential NF-Ybinding sites ( Supplementary Fig.…”
Section: P53 Mutation Leads To Upregulation Of Zdhhc5 Via Nuclear Tramentioning
confidence: 99%